Working Through Collective Trauma: Metafiction, Intertextuality, and the Need for Externalization and Relativization of Trauma in "The Virgin Suicides" - Vanyova Kostova, Bilyana (Estudios Ingleses de la Universidad Complutense, 2013)
In a period when Trauma Studies have been assuming more and more importance, Jeffrey Eugenides’s first novel, The Virgin Suicides (1993), happens to center precisely on the traumatic adolescent experiences of its protagonists. Its fragmented content mirrors the very structure of the dreamy narrative: after witnessing the Lisbon sisters’ mass suicide, the group of male narrators decides to tell a story truthful to their posttraumatic condition. This brings about the collective narrator’s failure to master the accuracy of the past events accompanied by their urge to recount the truth about the inexplicable suicides. In this paper, the novel is analyzed in terms of its connections with “another’s word”, to echo Bakhtin: on the one hand, the narrator negotiates with the community, with different kinds of written and oral accounts, even with their own childhood memories; on the other hand, the text communes intertextually with other texts. These connections help in the process of working through or coming to terms with trauma. It is argued that the path towards healthy mourning (as opposed to melancholia) must have recourse to the Other. In the novel, this is achieved via storytelling and subtle intertextual references to previous fictional works.